Association of serum selenium levels with diabetic retinopathy: NHANES 2011–2016 - Chen, Xi; Sun, Mei; Gu, Zhenzhen; Hao, Xiaofeng; Xie, Like (Frontiers in Medicine, 2025)
BackgroundSeveral studies have established a clear link between serum selenium levels and various health outcomes. However, to date, only a few studies have found an association between serum selenium levels and diabetic retinopathy (DR). The exact link between them is unclear. We collected data from different patient populations.MethodsData from 645 adults, collected through the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2016, were analyzed. The association between serum selenium levels and the incidence of DR was assessed using binary logistic regression. Subgroup analysis, smoothed curve-fitting analysis, and propensity score weighting were used to investigate the association further.ResultsAccording to the multivariate analysis, there was no statistically significant linear association between serum selenium levels and the probability of developing DR (p > 0.05). Segmented regression analysis, however, showed that the chance of developing DR was considerably lower when selenium levels reached the threshold of 106.8 μg/L (OR = 0.88, p = 0.0107).ConclusionA U-shaped curve represents the link between serum selenium levels and DR. The incidence of DR is elevated in individuals with serum selenium levels that are either higher or lower than the optimal range.